Pembuatan Biodiesel Dari Biji Kapuk (Ceiba Pentandra) Dengan Katalis Padat H-Zeolit - Afrielyanda H; Syaiful Bahri; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Biodiesel as alternative diesel fuel made from renewable biological resources, such as vegetable oils and animal fats. In Indonesia, the fuel consumption is increasing every year, so often there is a shortage of fuel. Therefore, the latest innovations necessary to produce alternative energy such as biodiesel. In this research, the conversion of cotton seed oil to biodiesel was performed by using catalyst